Liderazgo docente una actitud que transforma desde la cotidianidad de las Instituciones Educativas Francisco Palau y Quer y Tiquisio Nuevo (2016)
This is a research exercise of mixed type that identifies the necessary leadership attitudes in the fulfillment of teaching and is performed in two educational institutions of official character located in the southern department of Bolivar and other of private character in the Cesar department; it is developed through the analysis and triangulation of information obtained from the literature review of some studies empirically based in Chilean schools, applying two tests of leadership styles (know your leadership styles and evaluation of leadership competencies) to sixty teachers of these educational institutions and interview to 5 members in the educational community of each institution (one director, 2 teachers and 2 students). It was possible to investigate the styles most prevalent leadership in each institution, as well as to establish the own attitudes of teachers to realize and develop the practice of teaching, basis for strengthening this potential leadership, so that some recommendations are given. Grupo de Investigación: Estudios Interdisciplinarios sobre Educación (ESINED). -- Línea de Investigación: Gestión Educativa - Currículo. -- Área: educación. -- Tema: liderazgo docente.